TEXTBOOK DISCOURSE READABILITY: GENDER, READING INTEREST, AND SOCIO-ECONOMIC STATUS OF STUDENTS WITH POOR READING ABILITY - Sultan Sultan; Muhammad Rapi; Mayong Mayong; Suardi Suardi (Jurnal Cakrawala Pendidikan, 2020)
Textbook discourse readability is primarily determined by three key factors: the text, the writer, and the reader. Textbook discourse readability from the reader aspect especially among students with poor reading ability is rarely studied. Therefore, this study aimed to investigate textbook discourse readability among junior high school students with poor reading ability based on gender, reading interest, and family socio-economic status. A quantitative survey was conducted on 257 respondents from Indonesia. The data were gathered using a questionnaire and a cloze test. The results showed that textbook discourse readability on all investigated variables was categorized into the frustration level. There was a significant difference in textbook discourse readability among students with poor reading ability based on gender, reading interest, and family socio-economic status. Female students, students with high reading interest, students with well-educated mothers, students with parents earning more than seven million rupiahs (equals to USD480/month) were reported to have a higher textbook discourse readability. These findings suggest the importance of considering students’ individual characteristics and family socio-economic background in writing a textbook and designing reading instructions in junior high schools.